1995
DOI: 10.1016/s0969-2126(01)00270-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure and catalytic mechanism of glucosamine 6-phosphate deaminase from Escherichia coli at 2.1 å resolution

Abstract: From the similarities between the three presented structures, it is concluded that these represent the enzymatically active R state conformer. A mechanism for the deaminase reaction is proposed. It comprises steps to open the pyranose ring of the substrate and a sequence of general base-catalyzed reactions to bring about isomerization and deamination, with Asp72 playing a key role as a proton exchanger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
108
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 35 publications
4
108
0
1
Order By: Relevance
“…7A). Indeed a comparison of the crystal structure of 12 randomly selected proteins binding a phosphomonoester moiety or moieties shows that multiple hydrogen bonds are present between amino acid side chains and the phosphomonoester, which inevitably carries two negative charges (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Lysine and arginine residues form the positively charged binding pocket and often form the hydrogen bond donors as well, but other residues donating side chain hydrogen bonds also regularly occur.…”
Section: Discussionmentioning
confidence: 99%
“…7A). Indeed a comparison of the crystal structure of 12 randomly selected proteins binding a phosphomonoester moiety or moieties shows that multiple hydrogen bonds are present between amino acid side chains and the phosphomonoester, which inevitably carries two negative charges (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Lysine and arginine residues form the positively charged binding pocket and often form the hydrogen bond donors as well, but other residues donating side chain hydrogen bonds also regularly occur.…”
Section: Discussionmentioning
confidence: 99%
“…The highly clustered genes for this pathway were transcriptionally induced by (14). Previous studies have indicated that GlcN6P deaminase and the isomerase domain of GlcN6P synthase share some general similarities despite the lack of significant homology between their primary structures (21,31). Both proteins have related nucleotide-binding folds, although GlcN6P deaminase has a dehydrogenase-like six-stranded fold, whereas the fold of GlcN6P synthase is a five-stranded flavodoxin type.…”
Section: Discussionmentioning
confidence: 99%
“…Like most allosteric enzymes, GlcN6P deaminase has two extreme structural states, one displaying high substrate affinity, which is defined as the R state, and the other displaying low affinity for GlcN6P, the T state. The crystallographic structures of both the R and T forms of NagB have been solved, and the binding sites for GlcNAc6P and GlcN6P have been described (15,26). The transition from the T state to the R state, which activates the enzyme, can be driven by substrate binding that produces positive cooperativity (homotropic activation) and also by GlcNAc6P binding to the allosteric site (heterotropic activation).…”
mentioning
confidence: 99%
“…Mutants with conservative mutations (Tyr121Thr, Tyr121Ser, Tyr121Trp, Tyr254Phe, and Tyr254Trp) were constructed and were found to have modified kinetics and to be affected both in substrateinduced positive cooperativity (homotropic effect) and in the affinity of the allosteric site for GlcNAc6P (1,23) (Table 4). However, when the crystal structures were obtained, it was clear that neither Tyr121 nor Tyr254 is directly involved in GlcNAc6P binding (15,26) and that these amino acids must contribute indirectly to GlcNAc6P binding at the allosteric site. Mutants with substitutions at both positions still displayed substrate (homotropic) cooperativity (although it was reduced for mutants with mutations at Tyr254) and were also allosterically activated by GlcNAc6P, but the effect was different.…”
mentioning
confidence: 99%